Quatrain Genre or Form? (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, some opinions about the form of quatrain in our classical literature and the genre of quatrain in modern Uzbek poetry are presented. The explanation of this question is based on the opinion of some literary scholars on the question of whether the net is a genre or a form, which has caused many disputes. In addition, the poetics of genres and forms used in contemporary poetry, theoretical foundations, and genre laws are discussed